THE INFLUENCE OF PRINCIPAL LEADERSHIP AND ENGAGEMENT OF SCHOOL COMMITTEE TOWARD THE EFFECTIVENESS OF IMPLEMENTING SCHOOL-BASED MANAGEMENT : Descriptive Study at Public Elementary Schools in Coblong Sub-district, in Bandung City, Indonesia - Somoeun, Mut (2014)
Manajemen berbasis sekolah (MBS) adalah reformasi pendidikan melalui desentralisasi otoritas pengambilan keputusan dari kantor pusat ke sekolah-sekolah lokal. Namun, efektivitas pelaksanaan MBS didasarkan pada kepemimpinan kepala sekolah dalam menjalankan peran dan tanggung jawab dan partisipasi darikomite sekolah. Tujuan dari penelitian ini adalah untuk menganalisis bagaimana pengaruh kepemimpinan kepala sekolah dan keterlibatan komite sekolah telah menerapkan di sekolah dasar negeri di Kecamatan Coblong di kota Bandung. Metode yang digunakan dalam penelitian ini adalah pendekatan deskriptif-kuantitatif dengan teknik perhitungan statistik dan korelasi analisis data. Data dikumpulkan dengan memberikan kuesioner kepada 72 responden (36 kepala sekolah dan 36 komite sekolah) dengan populasi 36 sekolah dasar negeri. Kuesioner tertutup-berakhir digunakan dengan lima pilihan dari Likert Scale berfokus pada tiga dimensi peran utama kepala sekolah, termasuk: kepemimpinan instruksional, kepemimpinan masyarakat, dan visioner kepemimpinan; dan lima dimensi peran utama komite sekolah, termasuk: kebijakan pembuatan sekolah, penilaian kebijakan, penyediaan sumber daya keuangan, humas, dan perencanaan dan evaluasi pendidikan. Hasil penelitian ini menemukan bahwa: (1) pengaruh kepemimpinan kepala sekolah memiliki dampak yang tinggi(36.24%) pada efektivitas pelaksanaan manajemen berbasis sekolah; (2) keterlibatan komite sekolah memiliki dampak yang tinggi(37.45%) pada efektivitas pelaksanaan manajemen berbasis sekolah; dan (3) kedua pengaruh kepemimpinan kepala sekolah dan keterlibatan komite sekolah memiliki dampak yang tinggi (49.14%) pada efektivitas pelaksanaan manajemen berbasis sekolah. Hasilnya dapat disimpulkan bahwa 'pertunjukan dan komite sekolah' para pelaku partisipasi di sekolah-sekolah dasar negeri di Kecamatan Coblong di kota Bandung berada pada tingkat tinggi. Meskipun hasilnya baik, baik komite sekolah dan sekolah harus lebih memperkuat peran kunci dan tanggung jawab untuk meningkatkan perbaikan sekolah yang lebih baik. School-based management (SBM) is an educational reform through decentralizing the decision-making authority from the central office to local school. However, the effectiveness of SBM implementation is based on principal leadership in performing roles and responsibilities and participation of school committee. The purpose of this study is to analyze how the influence of principal leadership and engagement of school committee have been implementing at the public elementary schools in Coblong sub-district in Bandung city. The method used in this study is the descriptive-quantitative approach with techniques of statistical calculation and correlation of data analysis. The data are collected by giving questionnaires to 72 respondents (36 principals and 36 school committees) with population of 36 public elementary schools. The closed-ended questionnaires are used with five options of Likert Scale by focusing on three dimensions of principal's major roles, including: instructional leadership, community leadership, and visionary leadership; and five dimensions of school committee's major roles, including: making school policies, policy appraisal, provision of financial resources, public relation, and educational planning and evaluation. The results of this study found that: (1) the influence of principal leadership has high impact (36.24%) on the effectiveness of implementing school-based management; (2) the engagement of school committee has high impact (37.45%) on the effectiveness of implementing school-based management; and (3) both the influence of principal leadership and engagement of school committee have high impact (49.14%) on the effectiveness of implementing school-based management. Based on results, it can be concluded that the principal' performances and school committees' participations at those public elementary schools in Coblong sub-district in Bandung city are at high level. Although the results are good, both principal and school committee should more strengthen their key roles and responsibilities for enhancing better school improvement.